Wnt/β-Catenin Signaling as a Driver of Hepatocellular Carcinoma Progression: An Emphasis on Molecular Pathways - Deldar Abad Paskeh, Mahshid; Mirzaei, Sepideh; Ashrafizadeh, Milad; Zarrabi, Ali; Sethi, Gautam (Journal of hepatocellular carcinoma, 2021)
Liver cancers cause a high rate of death worldwide and hepatocellular carcinoma (HCC) is considered as the most common primary liver cancer. HCC remains a challenging disease to treat. Wnt/β-catenin signaling pathway is considered a tumor-promoting factor in various cancers; hence, the present review focused on the role of Wnt signaling in HCC, and its association with progression and therapy response based on pre-clinical and clinical evidence. The nuclear translocation of β-catenin enhances expression level of genes such as c-Myc and MMPs in increasing cancer progression. The mutation of gene encoding β-catenin and its overexpression can lead to HCC progression. β-catenin signaling enhances cancer stem cell features of HCC and promotes their growth rate. Furthermore, β-catenin prevents apoptosis in HCC cells and increases their migration via triggering EMT and upregulating MMP levels. It is suggested that β-catenin signaling participates in mediating drug resistance and immuno-resistance in HCC. Upstream mediators including ncRNAs can regulate β-catenin signaling in HCC. Anti-cancer agents inhibit β-catenin signaling and mediate its proteasomal degradation in HCC therapy. Furthermore, clinical studies have revealed the role of β-catenin and its gene mutation ( ) in HCC progression. Based on these subjects, future experiments can focus on developing novel therapeutics targeting Wnt/β-catenin signaling in HCC therapy.